RBI'S REGULATORY FRAMEWORK: BALANCING STABILITY AND GROWTH IN INDIAN BANKING - Madiwalar, Meenaxi Shivappa (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Reserve Bank of India (RBI), as India’s central banking authority, plays a pivotal role in balancing financial stability with economic growth. Its regulatory framework is built upon a combination of microprudential, macroprudential, and developmental measures that aim to ensure a sound, resilient, and inclusive banking system. In a diverse and fast-growing economy like India’s, the central challenge lies in maintaining banking sector discipline while enabling the flow of credit necessary for growth and innovation. RBI’s framework includes capital adequacy norms under Basel III, the Prompt Corrective Action (PCA) mechanism, asset quality reviews, and dynamic provisioning norms to guard against systemic risks. Simultaneously, it fosters growth by encouraging financial inclusion, digital banking innovation, and calibrated deregulation. Through instruments like the Liquidity Adjustment Facility (LAF), Statutory Liquidity Ratio (SLR), and repo operations, RBI manages liquidity to support economic activity while curbing inflationary pressures. Case studies such as the resolution of Yes Bank, the IL&FS crisis, governance actions against IndusInd Bank, and regulatory tightening on NBFCs illustrate how RBI has intervened decisively to contain risk while preserving market confidence. Moreover, its recent focus on digital banking norms, climate risk disclosures, and fintech oversight shows its adaptive approach in the face of emerging challenges. RBI's regulatory architecture has grown more proactive, data-driven, and responsive over time, incorporating stress testing, supervision technology (SupTech), and cross-sector coordination. This evolution reflects its aim to create a banking environment that is not only stable but also agile and growth-supportive. RBI’s ability to balance prudence with flexibility ensures that the Indian banking system remains robust in times of crisis and responsive during economic expansion, aligning with national development goals.